Preinfection process in cocoa fruits by Moniliophthora roreri - Flores, Dora (1994)
Moniliophthora roreri (Cif & Park) (Evans et al 1978) infects cocoa (Theobroma cacao L) fruits causing great losses. A study was conducted of the pathogen-host relationships on the fruit considering fungal spore distribution, germination, germ tube formation and infection using Scanning Electron Microscopy, Sixty-day-old fruits, inoculated and not inoculated, of cv. "Pound-7" (susceptible) and "UF-296' (moderately resistant) were collected from two sites of Costa Rica's low humid tropic, La Lola and Turrialba, Conidia were found mostly at the base of trichomes. Spores germinated similarly on both cultivars. Germination occurred through a polar germination pore or alternatively through the lateral spore wall 7-8 hr after inoculation of the fruits. The number of germinated spores was low, Germtube infection of the fruit via stomata was not common, Preliminary evidence suggests infection via direct penetration of epidemal cells and trichomes. Hyphae that emerged from the trichomes spread and infected other sites in the epidermis, including trichomes, stomata, injuries and other epidermal cells, Apressorium-like structures or terminal swellings on germ tubes were observed occassionally.